2010
DOI: 10.1142/s0217979210054579
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement in Two Qubit Magnetic Models With Dm Antisymmetric Anisotropic Exchange Interaction

Abstract: In the present paper, an influence of the anisotropic antisymmetric exchange interaction, the Dzialoshinskii-Moriya (DM) interaction, on entanglement of two qubits in various magnetic spin models, including the pure DM model and the most general XY Z model, are studied. We find that the time evolution generated by DM interaction can implement the SWAP gate and discuss realistic quasi-one-dimensional magnets where it can be realized. It is shown that inclusion of the DM interaction to any Heisenberg model creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…A minimal example of the DM model is the two-site model which has been studied to understand the overall dependence of quantities such as entanglement [45][46][47][48][49][50], quantum discord [51][52][53], and coherence [54] as a function of the various parameters of the system. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A minimal example of the DM model is the two-site model which has been studied to understand the overall dependence of quantities such as entanglement [45][46][47][48][49][50], quantum discord [51][52][53], and coherence [54] as a function of the various parameters of the system. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Many spin chains with external magnetic filed and DM interaction have been investigated in varieties of configurations even at thermal conditions [22,23]. Spin chains have also been studied by taking as a bath in the form of spin chains with DM interaction [24][25][26][27][28][29][30]. It has been observed that in some cases the DM interaction enhance the entanglement present in quantum spin chains.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to Heisenberg interaction which would align the neighboring spins parallel or antiparallel according to the system is ferromagnetic or antiferromangetic, respectively, DM interaction would align them perpendicular to one another. Since such spin alignments are possible to increase entanglement, it turns out that DM interaction has a significant effect on entanglement properties [46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%